1215 IMPROVING THE QUALITY OF ANTICIPATORY CARE PLANNING FOR PATIENTS WITH RECURRENT ASPIRATION PNEUMONIA. (16th January 2023) - Johnson, E; Ford, J; Perera, S A U; Nashed, N; Lovick, S; Mulkerrin, S; Bryant, E; Martin, L
Abstract: Introduction: Recurrent episodes of aspiration pneumonia (RAP) are a significant problem in frail patients leading to high re-hospitalization and mortality. Anticipatory care planning (ACP) enables improved quality of life and end of life care. We reviewed the assessment, ACP discussions and communication with Primary Care in these patients. Methods: We used a PDSA methodology, reviewing 116 patients with RAP referred to Speech and Language Therapy (SLT) in Elderly Medicine wards over six months, including the winter. Educational interventions were implemented. An illustrative case and pre-intervention results were presented at an online hospital-wide seminar and subsequently at an online departmental medical staff teaching session. Post-intervention analysis of 10 patients with RAP admitted over two summer months was conducted. The second round of interventions included departmental induction teaching for newly rotated doctors and creating an electronic ACP document (RAP ACP) for inclusion within the medical record. Results: Baseline data was collected from 116 patients (mean age 85, 47% female). After the educational interventions, data was collected from 10 patients (mean age 88, 70% female). Data is being collected from winter months after the second intervention. This will be available before the conference. Baseline data demonstrated the need for improvements in documentation of Mental Capacity Assessment (MCA) specific to feeding (21.5%), ACP completion (26.7%) and flagging patients suitable for the Gold Standards Framework (GSF) on discharge (15%). Following educational interventions, there was a substantial improvement in MCA documentation (80%). Furthermore, there was a marked improvement in the completion of ACP discussions (70%). Communication of patients eligible for GSF was similar (14.2%) post-intervention. Conclusions: Educational interventions substantially improved the quality of individualised care provided to patients with RAP. Mortality was high in both groups, yet documentation of eligibility for GSF was low, prompting further interventions targeting discharge communication.